Insulin resistance, role of metformin and other non‐insulin therapies in pediatric type 1 diabetes. Issue 8 (23rd November 2015) - Bacha, Fida; Klinepeter Bartz, Sara
Abstract : Type 1 diabetes mellitus (T1DM) in youth is a challenging chronic medical condition. Its management should address not only the glycemic control but also insulin resistance and cardiovascular disease risk factors which are increasingly recognized to be present in youth with TID. Current knowledge on the mechanisms of insulin resistance in T1DM is reviewed. The use of adjunctive therapies that are beneficial to achieve adequate glycemic control while mitigating the effects of insulin resistance are discussed with a focus on metformin therapy and an overview of other new pharmacologic agents.